Multiple endocrine neoplasia type 1 with refractory hypoglycemia and lung and liver metastases: a case report - Wang, Yong (J Int Med Res, 2021)
BACKGROUND: Multiple endocrine neoplasia type 1 (MEN1) is a rare autosomal dominant genetic disease. MEN1 with multiple endocrine adenomatosis complicated by multiple endocrine tumors is often misdiagnosed or missed. Herein, we describe the first reported case of refractory hypoglycemia and liver and lung metastases in a patient with MEN1. Case presentation: A 40-year-old man presented with a 3-month history of intermittent palpitations, fatigue, and sweating. The patient had a history of prolactinoma resection and refractory hypoglycemia 2 years earlier. Analyses of blood samples showed a decrease in random and fasting blood glucose and an increase in prolactin (PRL). Computed tomography (CT) and magnetic resonance imaging scans revealed two substantial masses in the pancreas and large masses in the liver and lung. Positron emission tomography-CT images showed hypermetabolic masses in the pancreatic body and tail. The liver and lung lesions were also hypermetabolic. The pancreatic lesion was surgically removed, and pathology confirmed that the mass was MEN1. The liver and lung masses were confirmed as metastatic tumors. CONCLUSION: If clinicians better understand MEN1, they can obtain a detailed patient and family history during the initial visit, allowing earlier diagnosis and intervention and improved prognosis.